2016
DOI: 10.1371/journal.pone.0151408
|View full text |Cite
|
Sign up to set email alerts
|

Modified Early Warning Score (MEWS) Identifies Critical Illness among Ward Patients in a Resource Restricted Setting in Kampala, Uganda: A Prospective Observational Study

Abstract: IntroductionProviding optimal critical care in developing countries is limited by lack of recognition of critical illness and lack of essential resources. The Modified Early Warning Score (MEWS), based on physiological parameters, is validated in adult medical and surgical patients as a predictor of mortality. The objective of this study performed in Uganda was to determine the prevalence of critical illness on the wards as defined by the MEWS, to evaluate the MEWS as a predictor of death, and to describe addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 29 publications
6
72
1
5
Order By: Relevance
“…30 31 However, we found that the UVA score performed better than MEWS perhaps due to differences BMJ Global Health in age, chronic illness, respiratory compromise and HIV prevalence between the derivation cohorts. The importance of severity of illness scores in patients with infection was recently highlighted by the new consensus sepsis-3 definitions that incorporated mortality risk scores including qSOFA that were derived from large data sets from North America and Europe.…”
Section: Discussionmentioning
confidence: 68%
“…30 31 However, we found that the UVA score performed better than MEWS perhaps due to differences BMJ Global Health in age, chronic illness, respiratory compromise and HIV prevalence between the derivation cohorts. The importance of severity of illness scores in patients with infection was recently highlighted by the new consensus sepsis-3 definitions that incorporated mortality risk scores including qSOFA that were derived from large data sets from North America and Europe.…”
Section: Discussionmentioning
confidence: 68%
“…Mortality prediction scores to risk-adjust in research and quality improvement efforts must also be developed and validated in relevant populations [54,55]. Region-specific equations or adaptations for resource-limited settings can improve performance and facilitate implementation [55][56][57][58][59].…”
Section: Gaps In Evidence For Best Practicesmentioning
confidence: 99%
“…Region-specific equations or adaptations for resource-limited settings can improve performance and facilitate implementation [55][56][57][58][59]. Risk assessment tools, such as the Modified Early Warning Score, which might help triage critically patients and allocate resources [54] have shown conflicting results when applied in resource-limited settings and need additional modifications and validation [60,61].…”
Section: Gaps In Evidence For Best Practicesmentioning
confidence: 99%
“…23 Some studies employ MEWS to classify internal medicine patients at admission, [24][25][26] but some others highlight the need for improvement and extension of parameters to better classify these patients. 23,27,28 Much effort has recently been put by the UK National Health Service (NHS) into a standardized scoring system and, as a result, the national early warning score (NEWS) has been introduced.…”
Section: Discussionmentioning
confidence: 99%